Risk factors for craving and relapse in heroin users treated with oral or implant naltrexone - Hulse, G.; Ngo, H.; Tait, Robert (Elsevier Inc., 2010)
Background: Oral naltrexone effectively antagonizes heroin, but patient noncompliance limits its utility; sustained-release preparations may overcome this. Few data are available on optimal blood naltrexone levels for preventing craving and/or return to heroin use. This study assesses various risk factors, including blood naltrexone level, for heroin craving and relapse to illicit opioids. Methods: Heroin-dependent persons from a randomized controlled trial of oral versus implant naltrexone were followed up for 6 months. Thirty-four participants received 50 mg oral naltrexone daily, plus placebo implant; thirty-five participants received a single dose of 2.3 g naltrexone implant, plus daily oral placebo tablets. Results: Compared to oral naltrexone patients, implant naltrexone patients were significantly less likely to use any opioids and had one-fifth the risk of using heroin = weekly. Risk of = weekly heroin use increased by 2.5 times at blood naltrexone concentration < .5 ng/mL compared with < .5 ng/mL, with 3 ng/mL associated with very low risk of use. Craving remained near "floor" levels for implant patients but rebounded to higher levels among oral patients. Lower craving scores (= 20/70) predicted lower relapse risk. Noncompliance with daily oral formula, higher baseline craving, longer history of use, and being younger predicted higher craving at follow-up. Conclusions: Implant naltrexone was better associated with reduced heroin craving and relapse than oral naltrexone. Effective treatment was achieved at blood naltrexone levels of 1 ng/mL to 3 ng/mL, with higher levels associated with greater efficacy. Craving assessment may be valuable in predicting relapse risk allowing timely intervention. © 2010 Society of Biological Psychiatry.